A Thematic Analysis of Overdose Prevention and Response Efforts in States Experiencing Declines in Rates of Opioid-Involved Overdose Deaths. (July 2022) - Robinson, Amber B.; Ali, Nida; Costa, Olga; Rooks-Peck, Cherie; Sorensen-Alawad, Amy; Ballard, Jonathan; Lowerre, Kathryn; Fondario, Anna
Objective: To address the opioid overdose epidemic, it is important to understand the broad scope of efforts under way in states, particularly states in which the rate of opioid-involved overdose deaths is declining. The primary objective of this study was to examine core elements of overdose prevention activities in 4 states with a high rate of opioid-involved overdose deaths that experienced a decrease in opioid-involved overdose deaths from 2016 to 2017. Methods: We identified 5 states experiencing decreases in age-adjusted mortality rates for opioid-involved overdoses from 2016 to 2017 and examined their overdose prevention programs via program narratives developed with collaborators from each state's overdose prevention program. These program narratives used 10 predetermined categories to organize activities: legislative policies; strategic planning; data access, capacity, and dissemination; capacity building; public-facing resources (eg, web-based dashboards); training resources; enhancements and improvements to prescription drug monitoring programs; linkage to care; treatment; and community-focused initiatives. Using qualitative thematic analysis techniques, core elements and context-specific activities emerged. Results: In the predetermined categories of programmatic activities, we identified the following core elements of overdose prevention and response: comprehensive state policies; strategic planning; local engagement; data access, capacity, and dissemination; training of professional audiences (eg, prescribers); treatment infrastructure; and harm reduction. Conclusions: The identification of core elements and context-specific activities underscores the importance of implementation and adaptation of evidence-based prevention strategies, interdisciplinary partnerships, and collaborations to address opioid overdose. Further evaluation of these state programs and other overdose prevention efforts in states where mortality rates for opioid-involved overdoses declined should focus on impact, optimal timing, and combinations of program activities during the life span of an overdose prevention program.